Fantasional dalam Novel Haniyah dan Ala di Rumah Teteruga Karya Erni Aladjai - Firdhaus Budi Nyata (Departement of Mathematics Education, 2022)
This study aims to understand the structure of the story in the novel Haniyah and Ala di Rumah Teteruga by Erni Aladjai with the narrative approach of Tzvetan Todorov's fantastical story. The purpose of fantastics is to interpret reality. Where the tension of something unreal collides with the existing reality. As a fantastic story, the novel